Morphological Study of Length, Breadth and Thickness of the Ovary at Different Age Group in Bangladeshi People - Ahmed, Md Shibbir; Khalil, Mohsin; Rahman, Md Babibur; Mannan, Sabina; Sultana, Seheli Zannat; Ara, Zubaida Gulshan; Rahman, M Mahbubur (Journal of Bangladesh Society of Physiologist, 2008)
The morphological study was done to see length, breadth and thickness of the ovary in different age group of Bangladeshi people to increase the knowledge regarding variational anatomy in our population. Sixty two postmortem tissue block containing ovary and fallopian tube along with surrounding structures were collected from 62 female cadavers of different age groups and fixed in 10% formol saline solution. Gross & fine dissections were carried out to study these morphological parameters of ovary in different age group. In the present study, findings were compared with the finding of other researchers. In this study the mean length of ovary was maximum in found in group C (46-80 years) 4.32cm and minimum was found in group A (2-13 years) 2.81cm of both side. The mean breadth of ovary was maximum in group C 2.01cm and minimum was in group A 1.38cm. The mean thickness of ovary maximum was in group C 0.971cm and minimum was in group A 0.682cm of both sides. In statistical analyses significant difference between two groups was calculated by using students ‘t' test. A difference between two groups was considered to be significant when p<0.05. In the present study it is observed that the size of the ovary is not equal on both side of same individual. Key Words: Ovary; Morphology; Bangladesh DOI:10.3329/jbsp.v2i0.980 J Bangladesh Soc Physiol. 2007 Dec;(2):24-27.